Implantation of a capsular tension ring during cataract surgery attenuates predicted remodeling of the post-surgical lens capsule along the visual axis - Ameku, Kurt A.; Berggren, Caleb C.; Pedrigi, Ryan M. (Frontiers in Bioengineering and Biotechnology, 2024)
Cataract surgery is a unique surgical procedure because it permanently alters the mechanical environment of the lens capsule by placing a hole in the anterior portion and implanting an intraocular lens (IOL) that has a very different geometry from the native lens. We hypothesize that this mechanical perturbation drives the long-term fibrotic behaviors of the remnant lens epithelial cells that can lead to pathological remodeling of the lens capsule and visual disturbances to the patient. In this study, we developed the first finite element-growth and remodeling (FE-G&R) model of the post-surgical lens capsule that was driven by altered stress to predict how different implants impacted evolving lens capsule mechanics and associated fibrosis over time after cataract surgery. We evaluated implantation of an IOL with and without a capsular tension ring (CTR). Our models predicted that implantation of a CTR with the IOL into the post-surgical lens capsule reduced the mechanical perturbation, thickening, and stiffening along the visual axis in both the remnant anterior and posterior portions compared to implantation of the IOL alone. This finding aligns with patient studies and suggests that implantation of a CTR with the IOL during routine cataract surgery would attenuate the incidence of visually-debilitating capsule fibrosis. Our work demonstrates that use of such modeling techniques has substantial potential to aid in the design of better surgical strategies and implants.